2021
DOI: 10.1021/acs.jpca.1c01563
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Dipole-Bound State in the 9-Phenanthrolate Anion by Photodetachment Spectroscopy, Resonant Two-Photon Photoelectron Imaging, and Resonant Photoelectron Spectroscopy

Abstract: Valence-bound anions with a dipolar core can support dipole-bound states (DBSs) below the electron detachment threshold. The highly diffuse DBS observed is usually of σ symmetry with an s-like orbital. Recently, a π-type DBS was observed experimentally in the 9anthrolate anion (9AT − ) and it was shown to be stabilized due to the large anisotropic polarizability of the 9AT core. To confirm the general existence of π-DBS and its structural dependence, here we report an investigation of the 9-phenanthrolate anio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 81 publications
1
20
0
Order By: Relevance
“…These experiments were conducted for two purposes: (1) to study the different threshold photodetachment behaviors of the two anions as suggested in the photon energy dependent PEI experiments presented above and (2) to search for dipole-bound excited states, which manifest themselves as near-threshold resonances for anions with polar neutral cores. [63][64][65][66][67][68][69] The photodetachment spectra for the two anions are shown in Fig. 6, where the arrows indicate the positions of the EAs measured from the high-resolution PEI experiments (Fig.…”
Section: Photodetachment Spectroscopy For Pyrrolide and Imidazolidementioning
confidence: 99%
See 1 more Smart Citation
“…These experiments were conducted for two purposes: (1) to study the different threshold photodetachment behaviors of the two anions as suggested in the photon energy dependent PEI experiments presented above and (2) to search for dipole-bound excited states, which manifest themselves as near-threshold resonances for anions with polar neutral cores. [63][64][65][66][67][68][69] The photodetachment spectra for the two anions are shown in Fig. 6, where the arrows indicate the positions of the EAs measured from the high-resolution PEI experiments (Fig.…”
Section: Photodetachment Spectroscopy For Pyrrolide and Imidazolidementioning
confidence: 99%
“…40,49 Here, we present a high-resolution PE imaging (PEI) study of cryogenically cooled pyrrolide and imidazolide anions produced from an electrospray ionization (ESI) source. The combination of high-resolution PEI 57,58 and cryogenically cooled ion trap, which operates at 4.6 K and can completely eliminate vibrational hot bands, [59][60][61][62][63][64][65][66][67][68][69] allow us to obtain accurate EAs and rich vibrational information for the pyrrolyl and imidazolyl radicals. The EAs of pyrrolyl and imidazolyl are measured accurately to be 2.1433 AE 0.0008 eV and 2.6046 AE 0.0006 eV, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30][31] In the same context, it is notable that the critical value of the dipole-moment for the existence of the π-type DBS is still in dispute. [32][33][34] Although the extent of the correlation effect is highly anticipated to be strongly dependent on individual chemical systems, the importance of the correlation effect in the DBS seems to be well received in the scientific community. Apparently, however, it is nontrivial to experimentally identify the correlation effect in terms of the static and/or dynamic role in the DBS.…”
Section: Introductionmentioning
confidence: 99%
“…The extra electron resides in a very diffuse orbital with low binding energy due to the shallow long-range electric dipole potential well. The dipole-bound state (DBS) can serve as the “doorway” of some electron attachment processes, and is important for varieties of biological molecules and interstellar molecules. , Theoretical investigations on the binding of an electron to an electric dipole dates back to 1947, when Fermi and Teller first gave the critical dipole moment of 1.625 D. , More refined calculations and experiments show that the empirical critical dipole moment for molecules to support a DBS is about 2.5 D. ,,, A real dipolar molecule usually has only one DBS due to the shallow potential well. However, theories predicted that a molecule with a large enough dipole moment could have more than one DBS. , The critical value for having an excited π-type DBS is 9.6 D, according to the results of the finite dipole model. ,, Up to now, almost in all experiments of polar molecules, only one DBS for each molecule has been observed, and it is σ-type, except the recent work by Yuan et al , They reported the existence of a π-type DBS indicated by photoelectron angular distributions of deprotonated 9-anthrol (9AT, C 14 H 9 O) molecular anions. The dipole moment of 9AT is 3.6 D, and only one DBS was observed.…”
mentioning
confidence: 96%